ANALISIS KOMPETITIF DAN TINGKAT EFISIENSI EKONOMI PADA USAHATANI UBI KAYU - zulkarnain zulkarnain (Jurnal WACANA PERTANIAN, 2019)
The purpose of the study was to determine the income of cassava farmers, the most influential production factors on cassava production, and the economic efficiency of cassava farming in Marga Tiga District, East Lampung Regency. The total population of 1.250 people who were taken using the Slovin formula, obtained a sample of 95 people using the Purposive Sampling method. The types of data are primary data and secondary data. Data analysis uses income analysis, multiple linear regression, and economic efficiency. The results of the study were 1) the income of cassava farmers was Rp. 7.422.769/ha, 2) the production factors of urea fertilizer, NPK fertilizer, SP3 fertilizer, ZA fertilizer and herbicides affected the production of cassava, and 3) the production factors of urea fertilizer, NPK fertilizer, SP36 fertilizer, ZA fertilizer and herbicide are not economically efficient, while the production factor of organic fertilizer is economically inefficient.